2022
DOI: 10.1155/2022/9974311
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Status Quo of Occupational Identity of Nursing Staff in Rehabilitation Department and Its Relationship with Work Stressors

Abstract: Due to the continuous progress of social economy, medical and health technology and the development of disciplines have shown a trend of rapid development. In the current medical environment, quality nursing services are constantly promoted. Nursing staff are dedicated to their work to the best of their ability. Meanwhile, they should be rewarded with corresponding happiness and joy in their work. This study starts from the perspective of nursing management and psychology. On this basis, it investigates the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some studies have shown that industrial and occupational tensions have a significant impact on people's burnout, and as a result, there is a low level of commitment, low efficiency, overwork, indifference, and burnout in the workplace [4]. In a survey of 153 neurologists on occupational fatigue, Jin Jing found that the current situation is not optimistic, with overtime work, frequent night shifts, failure of health checks, high work pressure and poor sleep quality being the main influencing factors [5]. A similar study by Prof. Max Denning also targeted the physical and mental health of healthcare workers during the prevalence of Covid-19, and the results showed that healthcare workers have a heavy burden of burnout, anxiety and depression [6].…”
Section: High-pressure Working Atmospherementioning
confidence: 99%
“…Some studies have shown that industrial and occupational tensions have a significant impact on people's burnout, and as a result, there is a low level of commitment, low efficiency, overwork, indifference, and burnout in the workplace [4]. In a survey of 153 neurologists on occupational fatigue, Jin Jing found that the current situation is not optimistic, with overtime work, frequent night shifts, failure of health checks, high work pressure and poor sleep quality being the main influencing factors [5]. A similar study by Prof. Max Denning also targeted the physical and mental health of healthcare workers during the prevalence of Covid-19, and the results showed that healthcare workers have a heavy burden of burnout, anxiety and depression [6].…”
Section: High-pressure Working Atmospherementioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%